Surgery An Introductory Guide - Sarpel, Umut (Springer New York : Imprint: Springer, 2014)
Surgery: An Introductory Guide is an all-in-one reference that provides the vital information needed to get the best learning experience out of an operation, and presents it in a convenient, efficient, and portable format.  Each section brings together the key points from several different fields including anatomy, pathophysiology, radiology, surgical technique, and clinical guidelines.  The operations covered represent the breadth of general surgery including hernia repair, cholecystectomy, breast surgery, general bowel surgery, and vascular surgery.  Each chapter provides informative text, bulleted lists, and common OR questions, combined with classic radiology images, diagrams, and a color illustration of the operative anatomy.  This method of using key words, high-yield diagrams, and illustrations enhances the ability to quickly absorb and retain the relevant information.  The volume is also organized by operation rather than by pathological topic, which lends itself to quick review before each case.    Written by Dr. Sarpel, a surgeon and former co-clerkship director who has been honored with multiple teaching awards, Surgery: An Introductory Guide is of great value to medical students and junior residents rotating on general surgery. .